2023
DOI: 10.1002/hbm.26498
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances the triangular association among behavior, resting‐state, and task‐state functional connectivity

Haoming Zhang,
Kun Chen,
Jin Bao
et al.

Abstract: Considerable advances in the role of oxytocin (OT) effect on behavior and the brain network have been made, but the effect of OT on the association between inter‐individual differences in functional connectivity (FC) and behavior is elusive. Here, by using a face‐perception task and multiple connectome‐based predictive models, we aimed to (1) determine whether OT could enhance the association among behavioral performance, resting‐state FC (rsFC), and task‐state FC (tsFC) and (2) if so, explore the role of OT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 111 publications
(179 reference statements)
1
0
0
Order By: Relevance
“…Network-level analyses that explored the effects of OT on the fine-grained level of brainwide connectivity patterns suggested that OT may broadly facilitate brain-wide exchange of information within and across networks particularly between the FPN and DMN in social fear contexts. The results align with recent findings suggesting that emotional processes such as fear and anxiety are processed in distributed networks and their interactions 27,34,97 as well as the distributed network-level properties and effects of the OT signaling system 41,98,99 . These findings underscore that OT may exert its effects on human emotion processing under complex naturalistic conditions via regulating extensive network-level interactions.…”
Section: Discussionsupporting
confidence: 91%
“…Network-level analyses that explored the effects of OT on the fine-grained level of brainwide connectivity patterns suggested that OT may broadly facilitate brain-wide exchange of information within and across networks particularly between the FPN and DMN in social fear contexts. The results align with recent findings suggesting that emotional processes such as fear and anxiety are processed in distributed networks and their interactions 27,34,97 as well as the distributed network-level properties and effects of the OT signaling system 41,98,99 . These findings underscore that OT may exert its effects on human emotion processing under complex naturalistic conditions via regulating extensive network-level interactions.…”
Section: Discussionsupporting
confidence: 91%
“…It is possible that a limitation of the study, the pooling of different parts of the mPFC, most importantly the prelimbic and infralimbic cortices masked the changes because the GABAergic systems of these otherwise adjacent brain regions differ from each other structurally and functionally [ 86 , 87 ]. In addition to the monoaminergic system, neuropeptides, e.g., oxytocin and corticotropin-releasing hormone, which we did not find to be altered in the present study, might also be involved in the control of prefrontal control of social interactions [ 88 , 89 ]. Finally, another limitation of the present study is, that only the medial prefrontal cortex was investigated while other brain regions also involved in the control of social behaviour, such as the striatum or the medial preoptic area, have not been investigated.…”
Section: Discussionmentioning
confidence: 86%